2012
DOI: 10.4103/0028-3886.105191
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between rs211037 of the GABRG2 gene and juvenile myoclonic epilepsy in Brazilian population

Abstract: These results present no evidence for an association of rs211037 with JME. Further studies are required to investigate the involvement of the GABRG2 gene in the genetic susceptibility to this epileptic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Allele frequency for the GABRG2 rs211037/C588T/Asn196Asn polymorphism showed differences in geographic distribution, race and origin of selected populations. An allelic distribution similar to that found in our study was reported in populations of Japanese and Chinese origin, as well as some European populations, with the T allele being more frequently highlighted in those with seizures (either IGE, FS, or both); these results are inconsistent with allele frequencies identified in populations from India, Germany and Nigeria [ 37 – 39 ].…”
Section: Discussionsupporting
confidence: 59%
“…Allele frequency for the GABRG2 rs211037/C588T/Asn196Asn polymorphism showed differences in geographic distribution, race and origin of selected populations. An allelic distribution similar to that found in our study was reported in populations of Japanese and Chinese origin, as well as some European populations, with the T allele being more frequently highlighted in those with seizures (either IGE, FS, or both); these results are inconsistent with allele frequencies identified in populations from India, Germany and Nigeria [ 37 – 39 ].…”
Section: Discussionsupporting
confidence: 59%
“…Demographic and clinical data of the unrelated patients with JME were reported previously [41]. Table 1 shows both allelic and genotypic frequencies of the studied polymorphisms in the two groups under study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, GABRG2 (rs211037) had a significant association with an Indian population but not in a Brazilian population. Interestingly, the allele and genotype frequencies of these polymorphisms show wide variation between the populations investigated, suggesting a role for ethnic differences in the distribution of this variant[63]. In these cases, the lack of replication could be caused by differences in the genetic structure of populations investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even though most researchers followed the ILAE clinical criteria, inconsistent interpretation of clinical parameters and electrographic findings could still contribute to the divergent results. For example, Balan et al[71] only used abnormal findings on EEG recordings to support JME diagnosis, while Gitaí et al[63] included generalized spike-wave discharges in their diagnosis. Moreover, JME is a heterogeneous electroclinical epilepsy syndrome[91,92].…”
Section: Discussionmentioning
confidence: 99%